Drug Induced Gangrene Of Forearm - Khan, Mumtaz (Journal of Postgraduate Medical Institute, 2011)
Novalgin has been used for many decades as antipyretic. It is known to cause serious toxic effects, particularly bone marrow depression. A case is reported where the drug has directly been implicated in causing gangrene of forearm in a young man. In search of a few books of Pharmacology and Therapeutics and some recent literature no such incidence was found, or reported before.